Use of Aluminum Alloy Plates as Externally Bonded Shear Reinforcement for R/C Beams - Abdalla, Jamal (2019)
Fiber Reinforced Polymers (FRP) and steel had proven to be very effective as externally bonded shear strengthening materials However, they both have their shortcomings. Recently developed high strength Aluminum Alloy (AA) plates possess desirable characteristics that may overcome some of the shortcomings of FRP and steel. The aim of this paper is to study the behavior of Reinforced Concrete (RC) beams strengthened with externally bonded AA plates as shear reinforcement. Three RC beams were designed to fail in shear and two of them were strengthened with externally bonded AA plates that were oriented at 90° and at 45°. The beams were tested under four-point bending until failure while magnitudes of loads and mid-span deflections were recorded. The results of the tested beams showed an increase in the load carrying capacity of up to 38% compared to the capacity of un-strengthened control beam. All beams failed in shear with diagonal shear cracks followed by de-lamination/de-bonding of AA plates near the support and near the applied load. This study demonstrated that AA plates can be used as externally bonded material to enhance the shear capacity of RC beams, however, further investigation is needed to further validate these results.